2018
DOI: 10.1177/0272431618776124
|View full text |Cite
|
Sign up to set email alerts
|

How Do Individual Predispositions and Family Dynamics Contribute to Academic Adjustment Through the Middle School Years? The Mediating Role of Friends’ Characteristics

Abstract: This study examined the mediating effect of friends' characteristics (problem behavior and academic achievement) in the association between students' background (family and individual factors) and later academic adjustment, as operationalized by problem behavior and academic achievement. We recruited 998 participants in three public middle schools and used three annual waves of data collection (Grades 6, 7, and 8). We found that students' own academic achievement and problem behavior are predictors of later ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 80 publications
1
5
0
3
Order By: Relevance
“…In terms of gender differences, the degree of student-perceived teacher aid and support is significant both for boys and girls, although girls tend to establish more positive relationships. This result is consistent with previous research indicating that girls tend to be socially more integrated at school [55], closer to teachers and with a better psychosocial adjustment in this context [30,56], thereby confirming the third hypotheses. Finally, it is important to note that although the effect sizes in the multivariate analyses of variance (MANOVAs) and in univariate analyses of variance (ANOVAs) are small, these results seem to maintain their importance in the field.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of gender differences, the degree of student-perceived teacher aid and support is significant both for boys and girls, although girls tend to establish more positive relationships. This result is consistent with previous research indicating that girls tend to be socially more integrated at school [55], closer to teachers and with a better psychosocial adjustment in this context [30,56], thereby confirming the third hypotheses. Finally, it is important to note that although the effect sizes in the multivariate analyses of variance (MANOVAs) and in univariate analyses of variance (ANOVAs) are small, these results seem to maintain their importance in the field.…”
Section: Discussionsupporting
confidence: 92%
“…Best friendships were measured by asking students to list one best friend (same-or cross-gender) in their grade during the fall semester (Urberg et al, 1997). Consistent with prior research, both reciprocated and unilateral best friendship nominations were included in analyses (Aloise-Young et al, 1994;Vaillancourt et al, 2019;Veronneau & Dishion, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Reciprocated nominations are considered important for identifying friendships (Rubin et al, 2009). However, some researchers suggest that peers who receive unilateral or nonreciprocal nominations still provide substantial influence, as they reflect an individual’s own perceptions of his or her relationships (Poulin & Chan, 2010; Vaillancourt, Paiva, Veronneau, & Dishion, 2019). For instance, Meter, Casper, and Card (2015) found that highly intimate, nonreciprocal best friendships (along with less intimate, reciprocal best friendships) influenced adolescents’ aggressive behavior.…”
Section: Peer Relations: Associations With Aggressionmentioning
confidence: 99%
“…One of them is the pubertal growth spurt which modifies adolescents' self-esteem and emotions, leading to changes in the way they interpret various events [55]. Other factors are changing external circumstances, such as transition to the next educational stage, and the need to adapt to the new requirements and the new peer environment [22,23,56,57]. Maxey and Beckert [11] stress the importance of relationships with parents, siblings, and friends; the impact of school; access to new technologies; and involvement in extracurricular activities, as factors that play a role in the psychosocial functioning of adolescents and affect their locus of control.…”
Section: Discussionmentioning
confidence: 99%